O148 SHORT-TERM RESULTS OF A RANDOMIZED CONTROLLED TRIAL OF STANDARD VS. PROLONGED TIME TO SURGERY AFTER NEOADJUVANT CHEMORADIATION FOR CANCER. (23rd November 2019) - Nilsson, K; Klevebro, F; ,; ,; Szabo, E; Halldestam, I; Johnsson, E; Wallner, B; Johansson, J; Johnsen, G; Aahlin, E K; Hjortland, G O; et al.
Abstract: Aim: The aim of this study was to clarify if prolonged time to surgery (TTS) improves postoperative outcomes in the curative intended treatment of an junctional cancer. Background & Methods: sophagectomy is conventionally performed 4-6 weeks after completed neoadjuvant chemoradiotherapy (nCRT). However, studies have shown that prolonged TTS might be favourable. A randomized multicentre clinical trial was performed with allocation to 4-6 or 10-12 weeks between finished nCRT and surgery. All patients received nCRT according to CROSS. Primary outcome of thstudy was postoperative. Smortality, need for intensive care, and length of hospital stay. Results: The study randomized 248 patients, 202have to date undergone esophagectomy 98 patients were allocated to prolonged TTS, and the groups were well matched concerning baseline characteristics. Postoperative complications were reported in 106 patients (52.5%).There was no difference in postoperative Clavien-Dindo score.In the standardgroup 17 (16.4%) patients had anastomotic leak compared to 19 (19.4%) in the prolongedgroup (P=0.572). Conduit necrosis was reported in 9 (4.5%) patients, esophago-bronchial fistula in 1 (0.5%) patient, chyle leak in 5 (2.5%) neumoni in 54 (26.7%) patients and respiratory insufficiency in 36 (17.8%) patients without significant difference . In the standard group 5 (4.8%) patients had postoperative mortality due to a complication, compared to 2 (2.0%) patients in the prolonged group (P=0.446). Median length of hospital stay was 14 days in the standard group and 17.5 days in the prolonged group (P=0.040). Conclusion: In this we found no significant differences in postoperative mortality comparing standard to prolonged TTS after nCRT. Although, an observandum is that the median length of hospital stay was significantly longer in the prolonged group. We need to compare response and survival to properly evaluate prolonged TTS, but these results suggest that timing is not cardinal in short-term postoperative outcomes.